Ubiquitous and pervasive computing concepts, methodologies, tools, and applications - Symonds, Judith, 1972-; IGI eBooks; IGI Global (Hershey, Pa. : IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2010)
With the development of ubiquitous and pervasive computing, increased and expanded adaptability to changing needs, preferences, and environments will emerge to further enhance the use of technology amongst global cultures and populations. This book covers the latest innovative research findings involved with the incorporation of technologies into everyday aspects of life from a collaboration of accomplished field experts. Providing an enriched compilation of authoritative industry solutions in ubiquitous and pervasive technologies, this 3-volume reference source presents academicians, researchers, and practitioners with a wide range of unique topics in one premier research collection.
Fundamental concepts and theories -- Development and design methodologies -- Tools and technologies -- Utilization and application -- Organizational and social implications -- Managerial impact -- Critical issues -- Emerging trends.
Includes bibliographical references and index.
Also available in print.
Mode of access: World Wide Web.
Title from PDF t.p. (viewed on July 26, 2010).
Keywords: Ubiquitous computing; Ambient intelligence; Location information management; Pervasive architecture; Pervasive computing; Pervasive healthcare; Smart embedded systems; Ubiquitous and pervasive application design; Ubiquitous communication infrastructure; Ubiquitous computing; Ubiquitous risk analysis; Ubiquitous services and business processes; Web-based human machine interaction; Electronic books